INTIMATE PARTNER VIOLENCE (IPV) IN PUNE, INDIA: A COMPARISON OF MALE AND FEMALE ATTITUDES, AND THE USE OF WAST TO MEASURE IPV AMONG INDIAN MEN - Chandra, Shivani (My University, 2016)
Intimate partner violence (IPV) includes physical, emotional, psychological and sexual abuse. The impact of IPV has become increasingly accepted as a significant public health problem worldwide. This manuscript thesis has two chapters which attempts to address the current gaps in IPV research in India. The first chapter compares people’s attitudes about IPV based on their gender, age, income and exposure to IPV. In order to better understand and compare men and women’s attitudes about IPV, 204 self-administered surveys were collected from the in- and out-patient clinics of the Sancheti Institute for Othopedics and Rehabilitation (SIOR), a hospital in Pune, India. The results of these surveys showed that men and older generations were more likely to agree that wife-slapping was a justified response to least one of the presented scenarios, and to support normatively prescribed rights of Indian husbands to have excessive power in a marriage. Income level and experience being a victim of IPV were not associated with attitudes towards IPV or husbands’ rights. The second chapter explores the use of the Woman’s Abuse Screening Tool (WAST) in a sample of 62 males. Results from the WAST indicated a 16% IPV prevalence rate. These two papers shed light on different aspects of IPV. Results from the first paper suggest that men and older generations should be targeted for educational initiatives aimed at reducing IPV. The second paper provides a much-needed estimation of IPV prevalence among Indian males. Together, these findings help close existing gaps in the literature regarding IPV in India.
Keywords: Intimate partner violence; IPV; Domestic Violence; India; WAST; IPV attitudes; Male victims of IPV